2022
DOI: 10.3389/fpls.2022.858477
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Expansion, and Divergence of ETHYLENE-INSENSITIVE 3 (EIN3)/EIN3-LIKE Transcription Factors During Streptophytes Evolution

Abstract: The transition of plants to land required several regulatory adaptive mechanisms. Little is known about these mechanisms, but they no doubt involved the evolution of transcription factor (TF) families. ETHYLENE-INSENSITIVE 3 (EIN3)/EIN3-LIKE (EIL) transcription factors (TFs) are core components of the ethylene signaling pathway that play important roles in almost every aspect of plant development and environmental responses by regulating the transcription of numerous genes. However, the evolutionary history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
0
7
1
Order By: Relevance
“…It can also be concluded that the evolutionary mechanism of the TraesTM9SF gene showed maintenance during the domestication of wheat. The finding, however, is contrary to the results of earlier studies, which have reported that gene duplications are a vital factor for genetic family expansion and plant function diversification ( Fang et al., 2022b ; Mao et al., 2022 ). The lack of gene duplication events in wheat TraesTM9SF genes poses exciting questions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It can also be concluded that the evolutionary mechanism of the TraesTM9SF gene showed maintenance during the domestication of wheat. The finding, however, is contrary to the results of earlier studies, which have reported that gene duplications are a vital factor for genetic family expansion and plant function diversification ( Fang et al., 2022b ; Mao et al., 2022 ). The lack of gene duplication events in wheat TraesTM9SF genes poses exciting questions.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the considerable number of TraesTM9SF genes in wheat relative to other plant species can be imputable to the complex genetic material of the wheat ( Brenchley et al., 2012 ; Chapman et al., 2015 ). Polyploidy events, such as genome duplication, have been demonstrated to contribute substantially to gene family expansion and functional heterogeneity in plants ( Soltis et al., 2015 ; Fang et al., 2022b ; Mao et al., 2022 ). The large-scale repertoire of TraesTM9SF genes in wheat can supply the crop with various functional capacities, enabling it to adapt to various ecological niches and endure diverse abiotic and biotic stresses ( Pont et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The EIL transcription factor family plays crucial roles in the regulation of several physiological and biochemical processes in plants [ 26 ]. However, the functions of EIL genes in the immunity of perennial woody plants have not been sufficiently examined.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, CTR1 phosphorylates EIN2 in the presence of ethylene, and this leads to EIN2 being cleaved so that the C-terminal part migrates to the nucleus ( Ju et al, 2012 , Qiao et al, 2012 , Wen et al, 2012 ) to activate the master transcription factor EIN3 ( Chao et al, 1997 ). Sequences of EIN3 and homologs (EIN3-LIKE; EILs) are present in genomes of land plants, but are also retrieved in genomic and transcriptomic data of several streptophyte algae ( Cheng et al, 2019 , de Vries et al, 2018a , Hori et al, 2014 , Ju et al, 2015 , Mao et al, 2022 ), but not in the streptophyte algal lineages Chlorokybophyceae and Mesostigmatophyceae and chlorophyte algae ( Mao et al, 2022 , Wang et al, 2015 , Wang et al, 2020 ). Therefore, based on sequence information and a few functional studies, we can conclude that the full ethylene signaling pathway was assembled in the common ancestor of Zygnematophyceae and land plants, and thus fully operational during the colonization of land by plants.…”
Section: Evolution Of Ethylene Signalingmentioning
confidence: 99%